Evaluation of Tribological Performance of Hydrogenated Dlc by Surface Texturing in the Presence of Palm Based Tmp Ester at Different Temperatures - Varman, Mahendra; Ahmed, Arslan; Masjuki, Haji Hassan; Abul kalam, Md.; Zulkifli, N. W.M. (ARCHive-SR, 2019)
Surface textured and DLC coated (hydrogenated amorphous carbon) samples were assessed for their coating performance at 40 oC, 80 oC and 125 oC. As a result, textured a-C:H DLC demonstrated higher but stable coefficient of friction (COF) at high temperatures as compared to un-textured DLC samples. However, textured DLC samples showed higher wear resistance compared to un-textured DLC coating. The enhancement can be elucidated by the lower graphitization of textured DLC samples.